Diagnosis Penyakit Kambing Menggunakan Metode Dempster-Shafer - Fibriliandani Nur Pratama; Nurul Hidayat; Suprapto Suprapto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
In meeting the needs of meat and milk in the country, developing goat Ranch has a good prospect because it also has opportunities as export commodities. However there are several factors which impede the goat breeders to find out what diseases are attacking their goat, i.e. the limitation of the time owned breeder, very expensive and the latter is at least a vet in remote areas. Information received from a veterinarian only in accordance with the conditions of the goats at the time. If there are other symptoms the next day then we must go back to the vet for consultation again. The theory of the Dempster-Shaffer is one method that is able to accommodate the uncertainty in the classification of multispectral. This theory is used to combine separate pieces of information to calculation the chances of an event. The required variable in this study is clinical symptoms on goats. The test results of this research show the system accuracy of 89%.